Study of Factors Linked to the Variation in Rentability in the Farming of Broiler Chickens in Northeast Algeria - Berghiche, A; Khenenou, T; Boualleg, I M; Bouacida, A; Labiad, I (Animal Review, 2018)
Obtaining good zootechnical performance in broiler chicken farming requires continuous and regular zootechnical and sanitary monitoring throughout the breeding period to increase its rentability. Our work carried out at the level of private broiler chicken farming in Eastern Algeria with the objective of comparing zootechnical performance during the breeding period with that obtained under the optimal conditions of strain ISA 15. Whose controlled and compared parameters show: a very high mortality rate- a very low weight evolution- a higher consumption index.